State-dependent modulation of positive and negative affective valences by a parabrachial nucleus-to-ventral tegmental area pathway in mice - Nagashima, Takashi; Mikami, Kaori; Tohyama, Suguru; Konno, Ayumu; Hirai, Hirokazu; Watabe, Ayako M. (Frontiers in Neural Circuits, 2023)
Appropriately responding to various sensory signals in the environment is essential for animal survival. Accordingly, animal behaviors are closely related to external and internal states, which include the positive and negative emotional values of sensory signals triggered by environmental factors. While the lateral parabrachial nucleus (lPB) plays a key role in nociception and supports negative valences, it also transmits signals including positive valences. However, the downstream neuronal mechanisms of positive and negative valences have not been fully explored. In the present study, we investigated the ventral tegmental area (VTA) as a projection target for lPB neurons. Optogenetic activation of lPB-VTA terminals in male mice elicits positive reinforcement in an operant task and induces both avoidance and attraction in a place-conditioning task. Inhibition of glutamic acid decarboxylase (GAD) 65-expressing cells in the VTA promotes avoidance behavior induced by photoactivation of the lPB-VTA pathway. These findings indicate that the lPB-VTA pathway is one of the lPB outputs for the transmission of positive and negative valence signals, at least in part, with GABAergic modification in VTA.